What’s new for IgA nephropathy part 2: clinical presentation, diagnosis, prognosis, treatment - Salvadori, Maurizio (Henry Stewart Talks, 2016)
Clinical presentation of IgA Nephropathy, Disease evolution, Histological presentation, Diagnosis, Prognosis, Histological markers, Oxford classification, Prognostic markers, Treatment, Non-immunosuppressive treatment, Steroid treatment